Targeted sanctions : the impacts and effectiveness of United Nations action - Biersteker, Thomas J.; Eckert, Sue E.; Tourinho, Marcos (Cambridge : Cambridge University Press, 2016)
International sanctions have become the instrument of choice for policymakers dealing with a variety of different challenges to international peace and security. This is the first comprehensive and systematic analysis of all the targeted sanctions regimes imposed by the United Nations since the end of the Cold War. Drawing on the collaboration of more than fifty scholars and policy practitioners from across the globe (the Targeted Sanctions Consortium), the book analyzes two new databases, one qualitative and one quantitative, to assess the different purposes of UN targeted sanctions, the Security Council dynamics behind their design, the relationship of sanctions with other policy instruments, implementation challenges, diverse impacts, unintended consequences, policy effectiveness, and institutional learning within the UN. The book is organized around comparisons across cases, rather than country case studies, and introduces two analytical innovations: case episodes within country sanctions regimes and systematic differentiation among different purposes of sanctions.
Machine generated contents note: Introduction Sue Eckert, Thomas J. Biersteker and Marcos Tourinho; 1. Thinking about United Nations targeted sanctions Thomas J. Biersteker, Marcos Tourinho and Sue Eckert; 2. The purposes of targeted sanctions Francesco Giumelli; 3. Security council dynamics and sanctions design Michael Brzoska and George A. Lopez; 4. United Nations targeted sanctions and other policy tools: diplomacy, legal, use of force Paul Bentall; 5. The relationship between United Nations sanctions and regional sanctions regimes Andrea Charron and Clara Portela; 6. Coordination of United Nations sanctions with other actors and instruments Alix Boucher and Caty Clement; 7. Implementation of United Nations targeted sanctions Enrico Carisch and Loraine Rickard-Martin; 8. The impacts of United Nations targeted sanctions Kimberly Ann Elliott; 9. The unintended consequences of United Nations targeted sanctions Mikael Eriksson; 10. The effectiveness of United Nations targeted sanctions Thomas J. Biersteker, Marcos Tourinho and Sue Eckert; 11. Institutional learning in targeting sanctions Peter Wallensteen; 12. Conclusion Thomas J. Biersteker, Marcos Tourinho and Sue Eckert; Appendix I. List of cases and episodes; Appendix II. Sanctions effectiveness; Appendix III. TSC database codebook; Appendix IV. Targeted sanctions consortium (TSC) participants.
Title from publisher's bibliographic system (viewed on 08 Mar 2016).
Keywords: elektronické knihy; electronic books; United Nations -- Sanctions; Sanctions (International law)